PERSEPSI MAHASISWA TERHADAP PENGGUNAAN ARTIFICIAL INTELLIGENCE DALAM PEMBELAJARAN DI UNIVERSITAS RIAU: penelitian deskriptif - Namira Ramadhani; Maisya Ratul Aini; Nayla Gusri Wulandari; Mamluatul Khoiriyah; Raihana Raisa; Rafi Hamdani; Hambali; Fitri Rahmatullaila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Many students use Artificial Intelligence in learning as a very efficient tool and increase the accessibility of information, in the learning environment gives rise to two conflicting narratives, there is a narrative that states Artificial Intelligence as a sophisticated tool in learning. However, behind that there are many concerns among students about the excessive use of Artificial Intelligence. The purpose of this study is to find out how the use of artificial intelligence in learning in higher education provides a number of significant benefits. The research technique was carried out by collecting interview data, in-depth with students of the University of Riau as well as documentation of data analysis and drawing conclusions. Research location The research was conducted at the University of Riau's main campus located at the Bina Widya Campus in Simpang Baru, Tampan District, Pekanbaru City, Riau Province. The research time is planned to take place around the end of October 2025. Some students stated that they were very happy to use Artificial Intelligence in lectures, however there were some students who were dissatisfied with Artificial Intelligence technology because it was too difficult to understand the language of the technology.